Analysis of Multiple Maximum Power Point Tracker Algorithm with Boost Converter in Photovoltaic System - Hasrolnizam, Muhammad Amiruddin; Yahaya, Jabbar Al-Fattah (Evolution in Electrical and Electronic Engineering, 2024)
This paper addresses the global need for increased energy efficiency in photovoltaic (PV) power generation through Maximum Power Point Tracking (MPPT) techniques—specifically Perturb and Observe (P&O) and Incremental Conductance (INC) integrated with a boost converter. The work focuses on improving PV system performance, facing challenges like low conversion efficiency and variable power generation. Objectives include creating a basic PV system, simulating P&O and INC algorithms in MATLAB Simulink, coding for Arduino, and assessing their performance under varying irradiance and temperature. The work utilizes a boost converter, MATLAB Simulink for simulation, and specific PV panel parameters which is 20W, 17V and 1.18A for each panel. It contributes insights into the comparative analysis of P&O and INC algorithms for optimizing PV system efficiency. Three PV panels is used for hardware and six PV panels is used in the simulation works. Arduino Mega 2560 is used as Pulse Width Modulation (PWM) generator in hardware implementation. The load used for simulation is 170Ω while load used for hardware is 88Ω. The results present a thorough study of PV system performance under changing conditions, showing that both algorithms effectively regulate voltage and current, though INC demonstrates a slight advantage in certain aspects. Hardware experiments yield promising results for both MPPT algorithms, with efficiency dropping under low irradiance conditions. It can be hard to compare because of the limitation of components available. This paper provides valuable insights into MPPT algorithm performance, emphasizing their strengths and limitations in different environmental conditions.